Aquatic exercise as medicine to treat women's pregnancy-related issues: mapping gaps and major findings - Azam, M.; Ali, A. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION: It is commonly known that pregnant women undergo physiological, psychological, pharmacological, metabolic, and morphological changes. Research shows pregnant women could benefit from exercise-based interventions (e.g., Chan, Au Yeung, & Law, 2019). Also, it is well established that expectant women participating in water aerobics improve their mental and physical health (Ali, Azam, & Askry, 2020). This study highlighted the gaps and conclusions of two systematic investigations on aquatic activities and psychophysical issues in pregnant women. Both of those investigations focused on aquatic activities and pregnant women.